2017
DOI: 10.1155/2017/8560652
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Low-Level Laser Therapy in Reducing Orthodontic Pain: A Systematic Review and Meta-Analysis

Abstract: Objectives. To assess the effectiveness of low-level laser therapy (LLLT) in reducing orthodontic pain after the application of orthodontic force (OF). Methods. A systematic search was conducted in the MEDLINE, EMBASE, Scopus, Cochrane Library, Web of Science, and EBSCOhost databases. The study included randomized clinical trials (RCT) which analysed the effectiveness of LLLT in reducing orthodontic pain assessed at 24 and 72 hrs after the application of OF. The risk of bias of the eligible trials was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
73
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 46 publications
(170 reference statements)
0
73
1
6
Order By: Relevance
“…Low-level laser therapy (LLLT) is one of the newer approaches proposed to control pain [19]. Lasers have been used in the medical and dental areas as an alternative to control pain [20][21][22]. They hold promise in controlling orthodontic pain because lasers do not have the side effect of the non-steroidal anti-inflammatory drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Low-level laser therapy (LLLT) is one of the newer approaches proposed to control pain [19]. Lasers have been used in the medical and dental areas as an alternative to control pain [20][21][22]. They hold promise in controlling orthodontic pain because lasers do not have the side effect of the non-steroidal anti-inflammatory drugs.…”
Section: Introductionmentioning
confidence: 99%
“…11 PBMT presents no serious side effects like those associated with NSAID therapy. 25 Further, some studies have shown that…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis, Andiappan et al reported that quality of life related with oral health in adolescents and adults, was higher in individuals who received treatment for malocclusion than in those who suffered malocclusion but did not undergo treatment. The beneficial effects of OT on dental aesthetics can be observed from the first few months; however it can also determine some unwanted effects in patients, such as pain (Deana et al, 2017) and anxiety (Long et al;Krishnan, 2018), thus diminishing the patient's quality of life during the OT. In order to estimate the impact of the placement of the first arch on the ability to carry out EDAs, we applied a questionnaire to patients undergoing OT in which we assessed functional limitation (Q2 and 3), physical incapacity (4), psychological disability (8, 9), physical pain (1, 5 and 6) and oral hygiene (7).…”
Section: Discussionmentioning
confidence: 99%